Adequação à legislação ambiental e qualidade da vegetação em propriedades rurais em Cerro Largo, RS - Almeida, Andressa de (2024)
The expansion in the agricultural area in Brazil has been remarkable, therefore, reconciling production and environmental conservation is one of the biggest challenges faced by the country. This study aimed to describe rural properties in the municipality of Cerro Largo - RS, regarding their compliance with the current environmental legislation, as well as analyzing the vegetation quality, using parameters defined by RESOLUTION 33/1994 of the National Council of Environment (CONAMA), regarding to the stages of forest succession in the state. Analyzes on compliance with legislation were carried out using data declared in the Rural Environmental Registry (CAR) and data available at Mapbiomas land cover map platform. Regarding the analysis of vegetation quality, 23 private properties were sampled, as well as 10 areas within a large forest block at Parque Estadual do Turvo (PET), which was used as a control group representing an area at advanced stage regadring ecological succession parameters for an area of seasonal deciduous forest in the state of Rio Grande do Sul. The parameters evaluated were: circumference at breast height (CBH), canopy height and coverage, litter abundance, incidence of light and presence of understory. Finally, vegetation quality was also evaluated using data collected by the LiDAR satellite on the forest height, where we also compared the vegetation within private areas in Cerro Largo with the vegetation of PET. Among the results achieved in this study, it is worth highlighting that more than half of the properties in the municipality did not declare any Legal Reserves (LR) or Permanent Protected Areas (PPA). Additionally, only 211 properties have the necessary amount of forest, which the legislation indicates in terms of LR and PPA. Overall, the municipality should have at least 2 400 hectares of PPA and 3 150 hectares of LR, and only 2 460 hectares of forest vegetation was detected on the Mapbiomas platform, that is, it is missing at least 3 090 hectares of forest in the municipality. We did not find significant differences between vegetation structure parameters between the Cerro Largo properties and the PET collected in the field, however the LiDAR data indicate that the PET has a higher and more homogeneous forest. Therefore, the structural parameters presented by RESOLUTION 33/1994 proved to be insufficient. Demonstrating that RESOLUTION 33/1994 is flawed and must be updated for the appropriate classification of ecological succession considering the seasonal deciduous forest in the state of Rio Grande do Sul.